Inhalation of (1→3)-β-D-glucan causes airway eosinophilia - Birgitta Fogelmark; Jörgen Thorn; Ragnar Rylander (Hindawi Limited, 2001)
Background: Moulds are present in a variety of environments and aerosols of fungal spores are generated when mouldy materials are handled. Molds contain (1→3)-β-D-glucan, a polyglucose which is present in the cell wall of fungi, certain bacteria and plants.